2004
DOI: 10.1152/japplphysiol.00024.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relocating to areas of reduced atmospheric particulate matter levels on the human circulating leukocyte count

Abstract: A high level of atmospheric particulate matter induces an increase in circulating polymorphonuclear leukocyte (PMN) counts and an increase in serum inflammatory cytokine levels. The particulate level in Antarctica is extremely low compared with that in industrial countries. We hypothesized that this low level would reduce circulating leukocyte counts and serum inflammatory cytokine levels in people visiting Antarctica from industrial countries. The number density of particulates with aerodynamic diameters of &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…The predominant pollutant during the forest fires was particles, and their levels relate temporally to changes in band cell counts. In contrast, reports from the United States (21) and Japan (22) showed a sharp decrease in circulating leukocyte counts and band cells that persisted over several months in subjects residing in Antarctica, where particulate levels are very low because of low levels of combustion of fossil fuels. These subjects also showed a subsequent increase in leukocyte and band cell counts on their return to Japan, and the leukocyte counts throughout the study correlate with the measured particulate levels (22).…”
Section: Lung Inflammation and Mobilization Of Leukocytesmentioning
confidence: 81%
“…The predominant pollutant during the forest fires was particles, and their levels relate temporally to changes in band cell counts. In contrast, reports from the United States (21) and Japan (22) showed a sharp decrease in circulating leukocyte counts and band cells that persisted over several months in subjects residing in Antarctica, where particulate levels are very low because of low levels of combustion of fossil fuels. These subjects also showed a subsequent increase in leukocyte and band cell counts on their return to Japan, and the leukocyte counts throughout the study correlate with the measured particulate levels (22).…”
Section: Lung Inflammation and Mobilization Of Leukocytesmentioning
confidence: 81%
“…Regarding pathway 2, pulmonary oxidative stress may be responsible for instigating the systemic CV pro-oxidative [61][62][63][64][65][66][67][68] and pro-inflammatory [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] chain reaction observed after PM exposure. Cardiac tissue oxidative stress increases within hours of PM 2.5 inhalation [61], whereas footprints (e.g.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…During the 12 month voyage from Japan to the Antarctic and back, the ship was equipped to measure PM continuously and the Physician on board was equipped to measure lung function with spirometry and collect regular blood samples from all 39 participants. In a study reported by Sakai et al 19 , it was shown (Fig. 3A) that the concentration of PM 2.5 fell from approximately 100,000/litre in Japan to just 1000/litre in Antarctica, remained at this level for the entire 12 months the group stayed in Antarctica, and returned to the control level during the return journey to Japan.…”
Section: The Host Response To Inhaled Particulate Mattermentioning
confidence: 76%
“…C) Segmented polymorphonuclear leucocyte (PMN) count, D) Band-form PMN count that indicates the early release of PMN of the marrow, and E) shows the monocyte counts, over the same time periods that the air pollution was measured. Although there were differences in leucocytes counts between smokers (red squares) and non smokers (purpletriangles) these differences (blue circles represent the difference between the two groups on which the differences over time were analyzed) tended to disappear in Antarctica where the levels of air pollution were very low (reproduced with permission from Sakai M et al 19 ). PM: particle matters; PMN: polymorphonuclear leucocytes.)…”
Section: The Host Response To Inhaled Particulate Mattermentioning
confidence: 99%